An Ultrasensitive, Visco‐Poroelastic Artificial Mechanotransducer Skin Inspired by Piezo2 Protein in Mammalian Merkel Cells. Issue 13 (10th February 2017) - Jin, Ming Liang; Park, Sangsik; Lee, Younghoon; Lee, Ji Hye; Chung, Junho; Kim, Joo Sung; Kim, Jong‐Seon; Kim, So Young; Jee, Eunsong; Kim, Dae Woo; Chung, Jae Woo; Lee, Seung Geol; et al.
Abstract : An artificial ionic mechanotransducer skin with an unprecedented sensitivity over a wide spectrum of pressure by fabricating visco‐poroelastic nanochannels and microstructured features, directly mimicking the physiological tactile sensing mechanism of Piezo2 protein is demonstrated. This capability enables voice identification, health monitoring, daily pressure measurements, and even measurements of a heavy weight beyond capabilities of human skin.